2007
DOI: 10.1080/08957340701431385
|View full text |Cite
|
Sign up to set email alerts
|

Alternate Assessments of Students with Significant Disabilities: Alternative Approaches, Common Technical Challenges

Abstract: This article examines three typical approaches to alternate assessment for students with significant cognitive disabilities-portfolios, performance assessments, and rating scales. A detailed analysis of common and unique design features of these approaches is provided, including features of each approach that influence the psychometric quality of their results. Validity imperatives for alternate assessments are reviewed, and approaches for addressing the need for validity evidence are outlined. The article con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…The states take several approaches to include portfolios, performance assessments, and rating scales (Elliott & Roach, 2007). The graduation outcomes also vary among the states, with 70% of states allowing students to earn a diploma after completing an alternate assessment (Thurlow et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The states take several approaches to include portfolios, performance assessments, and rating scales (Elliott & Roach, 2007). The graduation outcomes also vary among the states, with 70% of states allowing students to earn a diploma after completing an alternate assessment (Thurlow et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…In support of alternate assessments, Musson et al (2010) suggested that including students with disabilities in state assessments ensures that states consider those students when they make policy decisions. While Elliott and Roach (2007) supported the use of performance assessments and rating scale approaches over portfolio assessments, they suggested that only leaders in each state can make the decision about which approach works best for that state. Each state must determine for itself which alternate assessment to implement.…”
Section: Literature Search Strategymentioning
confidence: 99%
See 3 more Smart Citations